Assessing the effects of land transfer marketization on green total factor productivity from the perspective of resource allocation: Evidence from China - Jiang, Xu; Lu, Xinhai; Gong, Mengqi (Frontiers in Environmental Science, 2022)
Exploring the determinants of green total factor productivity (green TFP) is of great importance to economic performance and ecological sustainability. Based on the data of 30 provincial units in China from 2004 to 2016, this study analyzes the mechanism that land transfer marketization (LTM) affects green TFP through resource allocation firstly, then the regional resource allocation level is measured using the indicator of factor market distortion, and regional green TFP is estimated by the Slack-Based Measure (SBM) directional distance function and Malmquist-Luenberger (ML) index. On the basis of that, a panel threshold regression model is employed to empirically examine the theoretical mechanism that LTM affects green TFP through the intermediate variable of resource allocation. We find that there is one single threshold effect between LTM, resource allocation and green TFP taking resource allocation as the threshold variable. Specifically, while the degree of resource mismatch is lower than 0.1371, the coefficient of LTM on green TFP is 0.1553, otherwise, the coefficient changes to -0.2776. This study concludes that LTM would significantly increase green TFP when the degree of regional resource mismatch is below the threshold, otherwise, it would have an inhibitory effect on the development of green TFP. Besides, economic development level, R&D investment and infrastructure level can, to a certain extent, contribute to the improvement of green TFP. The findings have three important policy implications from land transfer policy of local governments, investment strategies of enterprises and differentiated policy services.